Circulating pro‐ and anti‐angiogenic mediators in patients infected with hepatitis C at different stages of hepatocellular carcinoma. Issue 7 (28th March 2014) - Talaat, Roba M.; Salem, Tarek A.; El‐Masry, Samir; Imbarek, Arafat; Mokhles, Mohamed; Abdel‐Aziz, Amal
<x xml:space="preserve">Abstract</x> Hepatocellular carcinoma (HCC) is a hypervascular tumor characterized by neovascularization. The objective of the current study was to determine circulating proangiogenic [vascular endothelial growth factor (VEGF), platelet derived growth factor (PDGF), and tumor necrosis factor (TNF‐α)] and antiangiogenic [IL‐4, IL‐12, interferon gamma‐induced protein 10 (IP‐10), and angiostatin] factors in Egyptian patients with different stages of HCC. Enzyme‐linked immunosorbent assay (ELISA) was used to detect the concentrations of these mediators in plasma of 135 HCC patients (57 Child‐Pugh A, 24 Child‐Pugh B, and 54 Child‐Pugh C stage) and 50 healthy subjects. Results showed a significant increase in plasma levels of VEGF (P < 0.001), PDGF (P < 0.001), TNF‐α (P < 0.01), angiostatin (P < 0.01), and IP‐10 (P < 0.001) and a significant reduction in IL‐12 (P < 0.001) in HCC patients in relation to normal controls. Classifying HCC patients based on their Child‐Pugh's score revealed that the maximum production of proangiogenic mediators (VEGF and TNF‐α) was present in HCC patients with Child‐Pugh C score which coincides with maximum reduction in antiangiogenic mediators (IL‐4, IL‐12, and angiostatin). Taken together, these results indicated that the determination of these factors in different Child‐Pugh's scores of HCC might be an important guide in clinical decision making regarding therapy and outcome. J. Med. Virol. 86:1120–1129, 2014. © 2014 Wiley Periodicals, Inc.